Konser Virtual sebagai Gaya Hidup Baru di Era Covid-19 - Fitrinanda An Nur; Indah Wenerda; Nur Fatonah; Yuana Palupi (LPPM Stikosa - AWS, 2022)
This study focuses on the virtual concert phenomenon as a new form of adaptation during the COVID-19 period. observe how media transitions affect communication processes and create new lifestyles. This pandemic era changed the order of human life in various social, cultural, and economic aspects. Humans must innovate in this era which then leads to the shift of humans in the use of communication and information technology. This research takes Prambanan Jazz as one of the biggest music concerts and has a cultural background. This international event is one of the biggest music concerts in Indonesia because it has cultural values as identity. Prambanan Jazz is now performing virtual concerts due to the pandemic. The year 2020 is the first year that Prambanan Jazz will perform its virtual concert. Therefore, it is necessary to examine the changes that occur in the communication process during this new model. This research is descriptive qualitative by using Convergence theory. Convergence sees that there is a shift and also the incorporation of old media into new media that can be accessed anywhere and anytime. Convergence offers easy access, and also brings new habits for people who can create new lifestyles. The results show that virtual concerts create a new lifestyle for people because of the transition from direct to indirect forms of communication.